KHAZANAH EKOLEKSIKON KEDANAUAN DALAM GUYUB TUTUR BAHASA BATAK TOBA - Johandi Sinaga; I Wayan Simpen; Made Sri Satyawati (Universitas Warmadewa, 2021)
This study aims to describe the ecolexicon treasures which represent the scope of Lake Toba. The ecolinguistic theory is used in this study. The data in this study are lexicons related to the scope of siltation. Data collection methods used are interview and observation methods. The analysis used a qualitative descriptive method. The results revealed 29 lexica related to the silt environment with three categories of ecolexicon entities namely flora ecolexicon, fauna ecolexicon, and fishing gear ecolexicon. The lexicon category consists of nouns and verbs. There are lexicon forms that are basic, derivative forms in the form of repeated words, and compound words. Keywords: Fishing Gear; Lake Toba; Ekoleksikon; Fauna; Flora